เรียลลิตี้โชว์ในประเทศไทย: ภาพสะท้อนศิลปะการแสดงผ่านสื่อในกระแสวัฒนธรรมบริโภคนิยม (REALITY SHOWS IN THAILAND: REFLECTIONS OF PERFORMING ART VIA MEDIA IN THE TREND OF CONSUMERISM CULTURE) - Sukbunjhong, Sammiti; Tunchareong, Viroon; Singyabuth, Supachai; Surasondhi, Kitima (วารสารศรีนครินทรวิโรฒวิจัยและพัฒนา สาขามนุษยศาสตร์และสังคมศาสตร์, 2012)
การวิจัยครั้งนี้มีวัตถุประสงค์ คือเพื่อศึกษาปฏิสัมพันธ์ระหว่างรายการเรียลลิตี้โชว์ในประเทศไทยกับกลุ่มคนและชุมชนในบริบทของวัฒนธรรมบริโภคนิยมของสังคมไทย ผู้วิจัยศึกษาพัฒนาการของเรียลลิตี้โชว์ในประเทศไทย โดยเน้นการศึกษาวิเคราะห์กรณีรายการอคาเดมี แฟนเทเชีย (ปฏิบัติการล่าฝัน) เนื่องจากรายการดังกล่าวเป็นรายการที่มีผู้ชมในประเทศให้ความนิยมสูงสุดและเป็นรายการที่มีบทบาททางสังคมอย่างต่อเนื่อง รวมถึงรายการดังกล่าวยังก่อให้เกิดการรวมกลุ่มคนที่มีความชัดเจนและเป็นรูปธรรมมากกว่าทุกรายการ การเลือกศึกษากรณีรายการเรียลลิตี้โชว์ อคาเดมี แฟนเทเชียนี้จึงสามารถนำไปสู่การอธิบายและทำความเข้าใจศิลปะการแสดงผ่านสื่อในภาพรวม เพื่อตอบวัตถุประสงค์ที่ผู้วิจัยตั้งไว้ ในด้านขอบเขตเรื่องพื้นที่และเวลา ผู้วิจัยเลือกศึกษาวิเคราะห์ข้อมูลที่สัมพันธ์กับเรียลลิตี้โชว์ในประเทศไทยโดยกำหนดช่วงเวลาและพื้นที่ศึกษา คือเริ่มตั้งแต่ปี พ.ศ. 2547 เป็นต้นมาจนถึงปัจจุบันซึ่งเป็นปีที่เรียลลิตี้โชว์อคาเดมี แฟนเทเชียเริ่มเผยแพร่สู่ผู้บริโภคในประเทศไทย นอกจากนี้ผู้วิจัยได้ศึกษาข้อมูลในวันประกาศผลการตัดสินผู้ชนะของรายการอคาเดมี แฟนเทเชีย เพื่อทำความเข้าใจปรากฏการณ์ รวมทั้งศึกษาข้อมูลในวันที่มีการจัดกิจกรรมที่จัดขึ้นหลังจบรายการเรียลลิตี้โชว์อาทิ มินิคอนเสริต์ และการจัดค่ายศิลปินอคาเดมี แฟนเทเชียพบแฟนคลับ เป็นต้น เพื่อเป็นประโยชน์ต่อการศึกษาพฤติกรรมของผู้ชมและศิลปิน รวมทั้งเพื่อนำข้อมูลมาใช้อธิบายวัตถุประสงค์ของการวิจัยในมิติเรื่องปฏิสัมพันธ์ระหว่างรายการเรียลลิตี้โชว์ในประเทศไทยกับกลุ่มคนและชุมชนในบริบทของวัฒนธรรมบริโภคนิยมของสังคมไทย ผลการวิจัยพบว่า เรียลลิตี้โชว์ในประเทศไทยได้ก่อให้เกิดชุมชนในความหมายใหม่ที่มีความแตกต่างไปจากความหมายในอดีต นอกจากนี้ชุมชนที่เกิดจากเรียลลิตี้โชว์ยังแสดงให้เห็นปรากฏการณ์ของการเคลื่อนที่ของผู้คนและวัฒนธรรมในโลกยุคใหม่ที่พรมแดนของชุมชนใดชุมชนหนึ่งเปิดกว้างและเชื่อมโยงติดต่อกับชุมชนอื่นๆ ได้อย่างรวดเร็วและหลากหลายรูปแบบมากขึ้น รวมทั้งเป็นชุมชนอันเกิดจากการรวมกลุ่มของบุคคลที่หลากหลายทั้งในด้านของภูมิหลัง วัย ฐานะ การศึกษา อาชีพ ตลอดจนพลังของทุนที่แตกต่างกันแต่มีความสนใจและมี ‘อุดมการณ์ร่วม’ ในสิ่งเดียวกันที่ปรากฏเกี่ยวกับรายการเรียลลิตี้โชว์อคาเดมี แฟนเทเชีย ชุมชนเรียลลิตี้โชว์เป็นชุมชนที่เกิดขึ้นจากการชมหรือบริโภคศิลปะการแสดงรูปแบบใหม่ที่มีการนำเสนอสิ่งที่เรียกว่า ‘ความจริง’ ผ่านสื่อ โดยสิ่งที่ปรากฏสู่สายตาผู้ชม คือ ภาพพฤติกรรมและปฏิกิริยาของผู้แสดงในรายการเรียลลิตี้โชว์ที่ผ่านกระบวนการประกอบสร้างความจริงจากฝ่ายทุนผู้ผลิตและทำหน้าที่กระตุ้นความรู้สึก และความต้องการของผู้ชม รวมทั้งขับเคลื่อนและสนับสนุนให้เกิดการสร้างความรู้สึกนิยมชมชอบและคลั่งไคล้ จนในที่สุดก้าวไปสู่ภาวะที่ผู้ชมต้องการการยึด ‘ผู้แสดง’ ในรายการเรียลลิตี้โชว์เป็นที่ยึดเหนี่ยวทางจิตใจหรือเป็นศูนย์กลางของการรวมกลุ่ม จนนำพาไปสู่การประกอบสร้างชุมชนที่เกิดจากการจินตนาการร่วมกันของผู้แสดง ผู้ชม และฝ่ายทุนผู้สนับสนุนให้เกิดกระบวนการบริโภคทุกองค์ประกอบที่เกี่ยวข้องของเรียลลิตี้โชว์ ปรากฏการณ์ที่เกิดขึ้นดังกล่าวคือ วัฒนธรรมไทยในบริบทของกระแสบริโภคนิยมที่สามารถขยายปริมณฑลของความเป็นสังคมบริโภคนิยมผ่านชุมชนจินตนาการที่มิได้จำกัดพื้นที่ทางด้านกายภาพ แต่สามารถส่งผ่านไปยังทุกส่วนทั้งในและต่างประเทศ คำสำคัญ: เรียลลิตี้โชว์ ศิลปะการแสดงผ่านสื่อ วัฒนธรรมบริโภคนิยม The purposes of this research is to study the interrelationships between reality shows in Thailand and the group of Thai people as well as the Thai community in the context of consumerism culture of Thailand. In execution, the researcher investigated the development of reality shows in Thailand by emphasizing analytical studies in the case of the show “Academy Fantasia (AF): An act of the Dream Catchers”. This is due to the fact that this show has gained highest popularity from Thai viewers and has had continuous social impacts and roles in Thai society. In addition, the show, more than any other shows, has brought about clear picture of gatherings of the group of Thai people. By studying this show, it will lead to explanation and understanding of performing art through media. In order to achieve the purposes of this research in terms of space and time, the research chose to conduct analytical studies in the data relating to reality shows in Thailand by indicating the period of time and the space for studies. The show started broadcasting to the consumers in Thailand at the period of time in the year 1995 (B.E. 2547) until the present time. Moreover, the research studied the data in time of the final round when there was an announcement of the show winner. Such study was pursued in an attempt to understand the phenomenon. The research not only covered the studies of that final round, but also the investigation of activities afterwards such as mini concerts as well as meet and greet sessions of AF artists and AF fan clubs, the investigation of which benefited in behavioral studies of viewers and artists, as well as in explanation of the interactions/interrelationships of the reality shows in Thailand and the group of Thai people as well as the Thai community in the context of consumerism culture of Thailand. The research results demonstrate that reality shows in Thailand brought about the gathering of Thai community in the new meaning which differed from that in the old days. Notwithstanding, the community originated from reality shows reflected the phenomenon of movements of people and culture in the new world where the border of one community opened and connected to the other communities with fast pace and with increasing variations of patterns. Such gatherings showed multi-dimensions of backgrounds, ages, socioeconomic statuses, educational attainments, occupations as well as sources of capitals, and yet had similar interests and “shared ideologies or ideals”. Phenomenon of AF reality shows has appeared from viewing and consuming performing arts in the new form of presenting “reality” through media. What appeared to the eyes of the viewers were the portrayal of behaviors and reactions of actors in reality shows, which has gone through the process of reality making from the production entrepreneurs. As such, it stimulated sentiments and desires/needs of viewers as well as moved and yielded to the feelings of likes and craves. As a result of such stimulations, the viewers were pulled onto the stage of attachments to those reality show actors, seeing them as asylum for souls and center of gatherings. Such phenomenon resulted in the community building which occurred by shared imaginations of actors, viewers and entrepreneurs. It is to note that entrepreneurs were the main factor in consuming processes for every component of reality shows. Such phenomenon was realized as Thai culture in the context of consumerism culture which has spread its realm of consumerism society through imaginations without limits of physical space and yet through every corners nationwide and abroad. Keywords: Reality Show, Performing Art via Media, Consumerism Culture